Routing Protocols under different Mobility Models, Node Density and Speed - Kumar, Deepak; Gupta, Suresh C. (Discoveries in Agriculture and Food Sciences, 2015)
Mobile Ad hoc NETwork (MANET) is self-organized and decentralized network. Due to these properties, they are usable in the field of disaster management, war scenarios, vehicular network etc. To send packets from source to destination, route(s) are required; to achieve this task routing protocols are designed. Routing protocols for MANET have been grouped into four types on the basis of single channel classification. These are Proactive, Reactive, Hybrid and Location-based/ Geographic. The performance of these protocols depends on various factors including mobility pattern/model, speed of node, density of node, area, transmission range etc. In this paper the factors taken into account are mobility models, speed of node and density of node. The performance metrics includes throughput, end to end delay and packet loss. The protocols simulated are DSR, LAR, OLSR and ZRP, choosing one from each group discussed above. The mobility models employed in this study are Random Way Point, Gauss Markov, Reference Point Group Mobility and Manhattan Grid. From the results it is evident that with the change in mobility pattern, speed and density of the nodes the performance varies. Furthermore it has been observed that location based routing protocols (LAR) and OLSR shows good performance with these variations.